DYNAMIC CONTACT PROBLEM OF WHEELS INTERACTION WITH RAILS - Starchenko, V. M.; Buriak, V. H. (Science and Transport Progress, 2005)
Results of theoretical research of a dynamic contact problem of interaction of a wheel with a rail are resulted, laws of change of the module of complex amplitude and a corner of shift of phases of fluctuations from dimensionless frequency and dimensionless weight are established.